THE VIABILITY OF PSYCHOEDUCATIONAL SCHOOL COUNSELLING PROGRAMS FOR REFUGEE STUDENTS IN MALAYSIA - Abu Bakar, Abu Yazid; Aissa, Ahmed Hamdi; Amat, Salleh (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
The aim of this paper is to explore the viability of psychoeducational school counseling programs for refugee students’ population in Malaysia. It is done by generally synthesizing the information gathered from literatures on the refugee phenomenon in Malaysia, the nature of psychoeducational programs provision in school settings, and the evolution of school counseling programs in Malaysia. The viability of psychoeducational school counseling programs for refugee students’ population in Malaysia was evaluated and discussed by integrating all the information gathered from this literature review analyses. The literatures’ syntheses provided baseline data to understand the possibility to establish appropriate psychoeducational and counseling programs for refugee school students in Malaysia.